Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s00167-021-06562-3
|View full text |Cite
|
Sign up to set email alerts
|

Glenoid concavity has a higher impact on shoulder stability than the size of a bony defect

Abstract: Purpose Surgical treatment of shoulder instability caused by anterior glenoid bone loss is based on a critical threshold of the defect size. Recent studies indicate that the glenoid concavity is essential for glenohumeral stability. However, biomechanical proof of this principle is lacking. The aim of this study was to evaluate whether glenoid concavity allows a more precise assessment of glenohumeral stability than the defect size alone. Methods The stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 32 publications
5
35
0
Order By: Relevance
“…The anatomy of glenoid concavity is a crucial factor contributing to glenohumeral stability. Loss of concavity, which was recently mathematically represented by the BSSR, is directly and linearly related to the loss of SR, a widely used biomechanical estimate for glenohumeral stability [ 4 , 5 ]. A deeper knowledge of the bony and osteochondral concavity distribution is essential to understand the important stability effect of the anatomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The anatomy of glenoid concavity is a crucial factor contributing to glenohumeral stability. Loss of concavity, which was recently mathematically represented by the BSSR, is directly and linearly related to the loss of SR, a widely used biomechanical estimate for glenohumeral stability [ 4 , 5 ]. A deeper knowledge of the bony and osteochondral concavity distribution is essential to understand the important stability effect of the anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have proposed formulas to estimate native glenoid width based on the length [ 24 , 25 ]. However, it has been shown that the width of bony defects has inaccurate information about stability [ 4 ]. The approximation of initial anteroposterior concavity by measuring only the superoinferior concavity in terms of BSSR or OSSR may be a more precise approach to manage the loss of bony glenoid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a rethinking process involving the impact of glenoid concavity has been initiated, challenging the current concept of determining a general threshold value for critical glenoid bone loss as a criterion for the use of a bone augmentation procedure in shoulder instability [ 16 , 22 ]. Ironically, previous work already demonstrated that the concave shape of the articular surface of the glenoid should be considered the crucial component for determining glenohumeral stability, which is based on the synergism with the rotator cuff via the “concavity compression” principle [ 14 , 26 ].…”
mentioning
confidence: 99%